2016
DOI: 10.1039/c5tc03368c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, electronic transport and optical properties of Si:α-Fe2O3 single crystals

Abstract: We report the synthesis of silicon-doped hematite (Si:a-Fe 2 O 3 ) single crystals via chemical vapor transport, with Si incorporation on the order of 10 19 cm À3. The conductivity, Seebeck and Hall effect were measured in the basal plane between 200 and 400 K. Distinct differences in electron transport were observed above and below the magnetic transition temperature of hematite at B265 K (the Morin transition, T M ). Above 265 K, transport was found to agree with the adiabatic small-polaron model, the conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
3
25
0
Order By: Relevance
“…It was found that with increasing temperature H SR decreases linearly. Similar values of H SR were observed by Rettie et al using anomalous hall effect measurement below the transition temperature T SR . However, above T SR , no spin reorientation was observed.…”
Section: Resultssupporting
confidence: 88%
“…It was found that with increasing temperature H SR decreases linearly. Similar values of H SR were observed by Rettie et al using anomalous hall effect measurement below the transition temperature T SR . However, above T SR , no spin reorientation was observed.…”
Section: Resultssupporting
confidence: 88%
“…The gold coating surface has high reflectivity yet is somewhat matte resulting in a ~91% Lambertian component. [7][8][9][10][11][12][13] A beamsteering mirror located within the sphere can be pointed down at the sample port, up at a fixed reference point, or at any angle on the sphere's front wall. Due to the horizontal position of the sample port at the bottom of the sphere, a glass cover is not necessary, which therefore removes the introduction of errors associated with the glass.…”
Section: Integrating Spherementioning
confidence: 99%
“…We have further applied the method to various samples such as hematite and investigated the difference in reflectance between visible and near infrared regions and mid-infrared regions. [9][10] Various spectral features can be observed in the infrared region depending on the particle size: the data presented in this paper are used to study in particular three types of spectral features: reststrahlen bands, Christiansen features, and transparency peaks. Christiansen minima have little to no absorption or scattering therefore radiation is able to pass through the sample, causing minimal to no reflectance, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations